Pengaruh Suhu dan Durasi pada Hasil Ekstraksi Ramah Lingkungan dan Aktivitas Antioksidan dari Stevia rebaudiana - Ismiarni Komala; Mariyatul Qibtiyah; Muthoharoh; Flori Ratnasari; Marvel (Fakultas Farmasi Universitas Andalas, 2025)
Stevia rebaudiana leaves are well-known for their intense natural sweetness, derived from steviol glycosides, which are 100-300 times sweeter than sugar. Besides being a natural sweetener, these leaves also hold the potential for various health benefits. This study compares two eco-friendly extraction methods: maceration using a water bath shaker (Dynamic maceration) and ultrasonic-assisted extraction in a water bath utilizing distilled water as the solvent. The objective was to assess their effects on extraction yield and antioxidant activity. Dynamic maceration was conducted at 25°C for 3 hours and 6 hours, yielding 14.2% and 15.5%, respectively, and at 75°C for 3 hours and 6 hours, yielding 18.6% and 16.7%, respectively. Ultrasonic-assisted extraction was carried out at 25°C for 30 minutes and 60 minutes, yielding 12.1% and 15.2%, respectively, and at 75°C for 30 minutes and 60 minutes, yielding 15.0% and 14.6%, respectively. The antioxidant activity of the extracts, assessed using the DPPH method at a concentration of 100 µg/mL, showed a linear trend corresponding to each extraction condition. For dynamic maceration, inhibition percentages were 33.4% (25°C, 3 h), 30.1% (25°C, 6 h), 25.9% (75°C, 3 h), and 16.7% (75°C, 6 h); for ultrasonic-assisted extraction, values were 39.9% (25°C, 30 min), 33.8% (25°C, 60 min), 31.8% (75°C, 30 min), and 27.1% (75°C, 60 min). The highest yield (18.6%) was obtained from dynamic maceration at 75°C for 3 hours, whereas the highest antioxidant activity (39.9%) was observed in ultrasonic-assisted extraction at 25°C for 30 minutes